On the dynamics of small and medium-sized enterprises: Evidence from Japan - Kazuo Yamada; Izidin El Kalak; Hidenori Takahashi (Asian Development Bank Institute (ADBI), 2018)
The main objective of this paper is to understand how the changes in the macroeconomic conditions (the global financial crisis) relate to the investment and financial decision-making for each of the different size categories of SMEs. To do so, we use a large dataset of 764,963 observations in Japan for the time period from 2006 to 2014. This large size of dataset enables us to understand the heterogeneity of SMEs on the financing and investment decision-making: such as the size, industry, and region. Our findings are of particular importance to regulators because they show that SMEs are dynamic in nature where they change their financial behavior in response to any macroeconomic shock. In addition, we report differences among the different size subsample at the sales growth and state/industry GDP growth levels; hence, this requires the design of a unique set of regulations for each group accordingly to properly enhance the growth potential for each group and for SMEs as a whole. Moreover, these findings have implications on lenders especially banks to treat each size group within SMEs differently while lending or assessing creditworthiness.
Keywords: G28; G32; G38; 330; SMEs; size categories; macro-economic shocks; investment; financing policy; Japan